An Exploration and an Application of the Recruitment Criteria on Qualified Personnel by the Analytic Hierarchy Process Method at Logistics Enterprises in Vietnam - Nong, Nhu Mai Thi; Ha, Son Duc (ExcelingTech, 2020)
This study aims to explore criteria for recruiting qualified personnel in logistics companies in Vietnam and apply these criteria into practical recruitment case by using a multiple decision-making method suggested by the authors. To explore recruitment criteria, the survey sample includes 224 logistics companies operating in one of the largest cities in Vietnam – Ho Chi Minh City. Cronbach’s Alpha testing methods and exploratory factor analysis (EFA) to test and build measurement scales are utilized. In addition, multiple linear regression method was used to find out the influence on recruitment selection decision. The research results show that there are four criteria affecting the decision to recruit qualified personnel including skills, knowledge, health, and personality traits. These criteria are then applied into personnel selection by using analytic hierarchy process method to select the best candidate. The paper offers practical help to industrial practitioners on their recruitment activities.